PRECONCENTRATION CU (II ) CATION EXCHANGER WITH PS- DVB- S03H IN A BATCH AND RECOVERY ANALYSIS BY ATOMIC ABSORPTION (EAAF ) - Zegarra P., Marixa (2013)
The presence of copper in nature is due to natural or anthropogenic sources. Because Peruvian law limits set quite low and instrumental techniques have limitations ultratrace levels , a method of preconcentration of aqueous samples of copper ( 11) with commercial cation exchange resin of the PS- DVB- S03H type is proposed and a batch system or " batch ." it worked with concentrations from 100 ppm to 0.01 ppm. the procedure followed is the same as determined by atomic absorption precedente2 article ( EAAF) and elution with 6N HCl , gave recoveries acceptable , obtaining an average percent recovery of about 85 % with a standard deviation of 3%.